Tailoring microstructure of silica xerogels via a facile synthesis approach - Pang, Suh Cem; Sze, Yun Kho; Suk, Fun Chin (University of Mohammed Premier Oujda, 2013)
Silica xerogels of tailored microstructure were prepared via a facile synthesis approach. This approach entails the preparation of silica nanoparticles using the sol-gel method under the influence of low frequency ultra-sonication. By applying optimum synthesis conditions, silica nanoparticles of tailored mean sizes in the form of silica sol type B (158.3 ± 14.1 nm), and silica sol type M (83.1 ± 22.5 nm) were successfully synthesized. The various mean particle sizes were then mixed in predetermined molar ratios, and subsequently gelation under controlled conditions. The effect of adding polyvinyl pyrrolidone (PVP) as a polymeric surfactant on the microstructure of silica xerogels was also investigated.